El ensilado como alternativa ambiental y económica en la transformación de la cascarilla de arroz como alimento de ganado en la provincia de san martín - Mendiola Céspedes, Anita Ruth (2013)
The research process was developed to take advantage of silage rice husk in cattle feed as an environmental and economic alternative. To obtain the silage was used as raw material rice husk, using as inoculum yogurt (Lactobacillus bulgaricus and Streptococcus thermophylus) was used as substrate and sucrose (cane sugar). To achieve the appropriate concentration of sucrose was used two dosages and dosage five were treated for 0, 5, 10, 15 and 20 wt%, and 0, 5, 7.5, 10 and 12.5 wt%. The matrix can be seen that the most important problems were burning pollution peel and rice straw. It was observed in the compositional analysis for both dosages proximal there is an increase in the protein value of higher sugar content in the sample, this was due to the conversion of carbohydrates by action of the bacteria present in the inoculum. The value of carbohydrate and fat also increased to higher percentage of sugar in the sample. The ash value tended to decrease with higher sugar concentration. It was concluded that it is feasible to convert rice husks into silage for cattle.